Beelden Buiten - Kröller-Müller Museum Otterlo. - van Straaten, Evert J. (Otterlo : Rijksmuseum Kröller-Müller, 1998)
Aeschbacher, Hans ; Althamer, Pawel ; Amado, Jean ; Andre, Carl ; Andreas, Tony ; Armitage, Kenneth ; Arp, Hans (Jean) ; Avramidis, Joannis ; Balka, Miroslaw ; Bourdelle, Antoine ; Brouwn, Stanley ; Buisman, Sjoerd ; Bustamente, Jean Marc ; Christo ; Costa, Joseph Mendes da ; Couzijn, Wessel ; Dodeigne, Eugène ; Dubuffet, Jean ; Ehrlich, Georg ; Epstein, Jacob ; Etienne-Martin, Henri ; Fabro, Luciano ; Riverhead (New York) ; Fontana, Lucio ; Fortuyn/O'Brien ; Freundlich, Otto ; Haber, Shamai ; Finlay, Ian Hamilton ; Hepworth, Barbara ; Houshiary, Shirazeh ; Huang Yong Ping ; Jespers, Oscar ; Kirkeby, Per ; Koch, Ödön ; Krop, Hildo ; Lavier, Bertrand ; Lee, U-Fan ; LeWitt, Sol ; van Lieshout, Joep ; Lipchitz, Jacques ; Maillol, Aristide ; Mark, Arno Van der ; Martini, Arturo ; Mascherini, Marcello ; Mastroianni, Umberto ; Merz, Mario ; Moore, Henry ; Morellet, François ; Müller, Pjotr ; van Munster, Jan ; Mutal, Lika ; Nash, David ; Noguchi, Isamu ; Nordman, Maria ; Oldenburg, Claes ; Pan, Marta ; Paolozzi, Eduardo ; Penalba, Alicia ; Penone, Giuseppe ; Permeke, Constant ; Polet, Johan ; Rädecker, John ; Reyers, Willem ; Richier, Germaine ; Richmond, Oliffer ; Rietveld, Gerrit Th. ; Rodin, Auguste ; Rogge, Cornelius ; Rückriem, Ulrich ; Serra, Richard ; Slegers, Piet ; Smith, Tony ; Snelson, Kenneth ; Strobos, Evert ; Suvero, Mark di ; Vandekop, David ; de Velde, Henry Van ; Verhulst, Rombout ; Visser, Carel ; Volten, André ; van der Weide, Albert ; Weiner, Lawrence ; Wenckebach, Oswald ; Wezelaar, Han ; Wiecek, Magdalena ; Wotruba, Fritz
biografie
Nederlands
boek